Frugivory and seed dispersal in the Galápagos: what is the state of the art? - Heleno, Ruben (2011)
The Galápagos are considered a model oceanic archipelago, with unique flora and fauna currently threatened by alien invasive species. Seed dispersal is an important ecosystem function with consequences for plant population dynamics and vegetation structure. Hence, understanding the seed dispersal abilities of the assemblages of frugivores will inform scientists and managers of the dynamics of plant invasions and improve management planning. Here we provide the first comprehensive review of published information on frugivory and animal seed dispersal in the Galápagos. We collected data from a variety of sources, including notes of the first naturalist expeditions, gray literature available only in Galápagos collections, and peer-reviewed journal articles. Plant-animal frugivorous interactions were retrieved from 43 studies and compiled into an interaction matrix describing 366 unique interactions. Most studies focused on fruit consumption as a driving force for natural selection, but seed fate was seldom considered. Although most (71%) of the interactions involved native plants, more than one-quarter (28%) involved introduced species. Interactions involving birds are considerably more common than those of reptiles and mammals, probably reflecting a research bias towards birds. Despite the historical importance of the archipelago as the laboratory for evolutionary and ecological research, understanding of its seed dispersal systems is limited. We end the review by suggesting 3 priority areas of research on frugivory and seed dispersal in the Galápagos: (i) target research to close knowledge gaps; (ii) the use of a network approach to frame seed dispersal at the community level; and (iii) evaluation of the effect of seed dispersal as a selective pressure acting upon plants and frugivores. Finally, the output of this research has to be properly delivered to the Galápagos National Park Services to help increase management effectiveness.